Fairgrounds: The Gateway to FAIR, Collaborative Agricultural Research - Introduction - Koo, Jawoo; Paul, Edie; Weber, Steffen; Moretto Embersics, Andre; Clevenger, James (International Food Policy Research Institute, 2025)
Fairgrounds is a collaborative, research platform redefining how agricultural data are accessed, shared, and applied. Built on FAIR principles (findable, accessible, interoperable, reusable), it connects CGIAR research with global data ecosystems to accelerate discovery, innovation, and impact. The platform provides access to thousands of digital assets from past and current research initiatives, operational systems, and public data hubs that span agronomic, climate, and genomic information.